2021
DOI: 10.1097/md.0000000000027420
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum uric acid levels as a predictor of future decline in renal function in older adults with type 2 diabetes

Abstract: Given that factors affecting renal function remain unknown, this study aimed to identify key predictors of estimated glomerular filtration rate (eGFR) deterioration, which is a representative of renal function decline in older adults with type 2 diabetes (T2DM). In an exploratory prospective observational study, we enrolled 268 Japanese people with T2DM aged ≥20 years who were followed up at Shinshu University Hospital. Among those, 112 eligible individuals aged ≥65 years were included in the present study. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Systolic blood pressure should be lower than 140 mm Hg, and diastolic blood pressure should be under 90 mm Hg to ensure a lower risk of microvascular disease (including DN) (De Boer et al, 2017;Shibata et al, 2021). Lower blood pressure targets ranging from 130 to 80 mm Hg may be recommended for a few patients (e.g., patients with known DN or higher risk of atherosclerotic cardiovascular ailments) if they can be met without severe treatment side effects.…”
Section: Blood Pressure Controlmentioning
confidence: 99%
“…Systolic blood pressure should be lower than 140 mm Hg, and diastolic blood pressure should be under 90 mm Hg to ensure a lower risk of microvascular disease (including DN) (De Boer et al, 2017;Shibata et al, 2021). Lower blood pressure targets ranging from 130 to 80 mm Hg may be recommended for a few patients (e.g., patients with known DN or higher risk of atherosclerotic cardiovascular ailments) if they can be met without severe treatment side effects.…”
Section: Blood Pressure Controlmentioning
confidence: 99%
“… 10 Firstly, the factors influencing rapid renal function decline remain controversial in the current document. 18 For example, some studies found that elevated SUA was related with a raising risk of renal disease onset and progression, 10 , 19 and with an increased rate of eGFR rapid decline. 20 , 21 By contrast, an association of SUA with CKD and with eGFR rapid decline was not demonstrated in other studies.…”
Section: Introductionmentioning
confidence: 99%
“…SUA affecting rapid decline in renal function remain controversial. 14 Moreover, most of the related studies used cross-sectional design, 13,[15][16][17] and only three studies were conducted to explore the influence of longitudinal SUA changes on the renal dysfunction in the general population of Japan and Thailand. 2,10,18 Therefore, our research contributed to exploring potential factors associated with rapid kidney function decline and new-onset kidney disease among Chinese elderly population, and to examine the relationships between baseline SUA, longitudinal change in SUA and rapid eGFR decline over 5 years for a Chinese elderly population with normal kidney function at baseline, which, to our knowledge, has not been explored in the existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…As the end product of purine metabolism, approximately two‐thirds of SUA is excreted by the kidneys 13 . In the current documents, whether SUA affecting rapid decline in renal function remain controversial 14 . Moreover, most of the related studies used cross‐sectional design, 13,15–17 and only three studies were conducted to explore the influence of longitudinal SUA changes on the renal dysfunction in the general population of Japan and Thailand 2,10,18 …”
Section: Introductionmentioning
confidence: 99%